Nontuberculous mycobacterial abscess of lacrimal sac and eyelid debridement: Case report - Toshihiko Matsuo; Takehiro Tanaka; Kiyoshi Yamada; Motoko Nose; Yasushi Tanimoto (Clinical Case Reports, 2023)
Key Clinical Message It is important to stain acid‐fact bacilli on the smear of abscess puncture in addition to Gram stain to detect nontuberculous and tuberculous mycobacteria in the early phase since both can cause rare and challenging extrapulmonary manifestations. Abstract A 56‐year‐old otherwise healthy woman developed abscess from dacryocystitis in the right lower eyelid. The smear of puncture fluid showed acid‐fast bacilli and Mycobacterium abscessus was identified after a month. The early start of clarithromycin/ethambutol was switched to clarithromycin/levofloxacin. Debridement specimen after 7‐month treatment showed granulomatous tissue with no bacilli.